A Review Paper on Comparative Study of FPGA Implementation of Adhoc Security Algorithms (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Nowadays data security is an important issue for decentralized networks like Adhoc Network. In this paper, we have proposed the study of five FPGA implementated data security algorithms specially designed for adhoc network. We have proposed the role of FPGAs within a security system and provided the solutions to security challenges. The result shows that FPGA implementation outperforms software and processors implementation by 20 and 140 times respectively.